Victimization Experiences and Executive Dysfunction as Discriminating Risk Indicators for Youth Offender Typologies. (January 2020) - Yoder, Jamie; Precht, Madison
Research is becoming increasingly nuanced in its examination of offenders, and thus typological distinctions according to generalist and/or specialization offense profiles may be notable for targeted intervention efforts within and between classifications of offenders. There is a significant body of evidence identifying early-life victimization and executive function deficits as critical developmental antecedents to sexual and non-sexual offending alike, but they have not been exhaustively evaluated as a discernable experience among criminally versatile offenders (youth who commit both sexual and non-sexual crimes). This study aims to address gaps by examining associations between early-life victimization, other traumatic experiences in the home, and executive functioning deficits and then test how disparate offending groups differentially experience these early risks. Using a sample of juvenile-justice-involved youth ( N = 200), who committed sexual only offenses ( n = 41), non-sexual only offenses ( n = 124), and criminally versatile offenders ( n = 27), multivariate analysis of variance tests and bivariate correlations were conducted. Results revealed that there were statistically significant correlations between measures of executive functioning and specific incidents of victimization, particularly sexual, physical, and emotional. There were also significant group differences in measures of sexual abuse, physical and emotional abuse, and executive functioning with criminally versatile offenders showing higher rates of physical and emotional abuse and sexual only offenders showing higher rates of sexual abuse and some executive functioning deficits. Practice and research implications are discussed.